Voxel-Based Analysis of Fractional Anisotropy in Post-Stroke Apathy - Yang, Song-ran (PLoS One, 2015)
OBJECTIVE: To explore the structural basis of post-stroke apathy by using voxel-based analysis (VBA) of fractional anisotropy (FA) maps. METHODS: We enrolled 54 consecutive patients with ischemic stroke during convalescence, and divided them into apathy (n = 31) and non-apathy (n = 23) groups. We obtained magnetic resonance images of their brains, including T1, T2 and DTI sequences. Age, sex, education level, Hamilton Depression Scale (HAMD) scores, Mini-Mental State Examination (MMSE) scores, National Institutes of Health Stroke Scale (NIHSS) scores, and infarct locations for the two groups were compared. Finally, to investigate the structural basis of post-stroke apathy, VBA of FA maps was performed in which we included the variables that a univariate analysis determined had P-values less than 0.20 as covariates. RESULTS: HAMD (P = 0.01) and MMSE (P<0.01) scores differed significantly between the apathy and non-apathy groups. After controlling for age, education level, HAMD scores, and MMSE scores, significant FA reduction was detected in four clusters with peak voxels at the genu of the corpus callosum (X = −16, Y = 30, Z = 8), left anterior corona radiata (−22, 30, 10), splenium of the corpus callosum (−24, −56, 18), and right inferior frontal gyrus white matter (52, 24, 18), after family-wise error correction for multiple comparisons. CONCLUSIONS: Post-stroke apathy is related to depression and cognitive decline. Damage to the genu of the corpus callosum, left anterior corona radiata, splenium of the corpus callosum, and white matter in the right inferior frontal gyrus may lead to apathy after ischemic stroke.